2021
DOI: 10.3390/biom11111638
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Alternative Procedures to Obtain Packed Red Blood Cells for β-Thalassemia Major Transfusion Therapy

Abstract: β-thalassemia major (βTM) patients require frequent blood transfusions, with consequences that span from allogenic reactions to iron overload. To minimize these effects, βTM patients periodically receive leucodepleted packed red blood cells (P-RBCs) stored for maximum 14 days. The aim of this study was to compare two alternative routine procedures to prepare the optimal P-RBCs product, in order to identify differences in their content that may somehow affect patients’ health and quality of life (QoL). In metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Analyses were carried out using a CELL-DYN Ruby Hematology Analyzer (Abbott Laboratories). Haemolysis was estimated following the Harboe direct spectrophotometric method, as already published [ 22 ]. Briefly, free haemoglobin (HbO 2 ) absorbance was measured at 415 nm (ε = 512 mM −1 cm −1 ); the percentage of haemolysis was derived using the free Hb concentration in the supernatants, the total Hb and the HCT.…”
Section: Methodsmentioning
confidence: 99%
“…Analyses were carried out using a CELL-DYN Ruby Hematology Analyzer (Abbott Laboratories). Haemolysis was estimated following the Harboe direct spectrophotometric method, as already published [ 22 ]. Briefly, free haemoglobin (HbO 2 ) absorbance was measured at 415 nm (ε = 512 mM −1 cm −1 ); the percentage of haemolysis was derived using the free Hb concentration in the supernatants, the total Hb and the HCT.…”
Section: Methodsmentioning
confidence: 99%
“…RBC count and Hgb content were found to be higher in method one, while PRBCs obtained with method two contained less potassium, iron, and oxidative stress markers. The authors concluded that more clinical studies considering the possible long‐term consequences of these differing aspects should be done with thalassemia patients 19 …”
Section: Blood Safetymentioning
confidence: 99%
“…The authors concluded that more clinical studies considering the possible long-term consequences of these differing aspects should be done with thalassemia patients. 19…”
Section: Schiroli Et Al Performed a Comparison Of Two Alternative Pro...mentioning
confidence: 99%
“…The disease is characterized by wide genotypic and phenotypic variability: the heterozygous state, which was previously considered a “minor” form of β-thalassemia, is usually asymptomatic and causes only mild anemia. On the other hand, homozygosis may result in β-thalassemia “intermedia”; which ranges in clinical severity from asymptomatic to transfusion-dependent forms, or in β-thalassemia “major”; which is the more severe disease, leading to a serious form of anemia in which survival is possible only with regular blood transfusions [ 3 , 4 ]. In the latter case, chelation therapy is required in order to reduce the adverse effects of iron overload due to red blood cell transfusions.…”
Section: Introductionmentioning
confidence: 99%